Preface of the International Coffee Convention 2024 (ICC2024) - Steffen Schwarz; Dirk W. Lachenmeier (Proceedings)
The 2nd International Coffee Convention 2024 (ICC2024), scheduled for 17–18 October 2024, in Mannheim, Germany, seeks to advance the discussions from the successful ICC2023 [...]